Menjawab Tantangan Pelaksanaan Penagihan Pajak Menuju Reformasi Perpajakan Indonesia - Ariefina Sri Indaryani; Aniek Juliarini (Universitas Trunojoyo Madura, 2020)
Tax collection realization at Kanwil DJP Jateng II in 2018 increased sharply, but tax arrears were still large. This study analyzed the challenges faced in implementing tax collection, finding the efforts that have been made to overcome them, and formulating what is needed to optimize tax collection. The study was descriptive qualitative. Primary data, secondary data, and literature studies were used. Primary data were obtained from questionnaires filled by Bailiff and Head of Tax Collection Section, and interviews with the tax officials. Secondary data were obtained from reports and other data. Results showed that the three biggest challenges were: HR, both in quantity and quality; administration, in the form of incomplete or invalid data; and difficulty in finding the taxpayer and the risk of a lawsuit. The efforts that have been made were: increasing the competencies of both hardskill and soft skills; internal coordination, especially with account representatives and tax auditors; management of tax arrears, and conduct coordination with related stakeholders. Things that need to be done to improve tax collection performance are: data accessibility, Bailiff protection, infrastructure, regulations and applications, position and remuneration certainty, and competence.